2016
DOI: 10.1128/aem.01051-16
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Amine-Oxidizing Dairy Lactic Acid Bacteria and Identification of the Enzyme and Gene Involved in the Decrease of Biogenic Amines

Abstract: Because high concentrations of the potentially toxic biogenic amines may be found in traditional/typical cheeses, the safety of these food items should be improved. Lactic acid bacteria selected for the ability to degrade biogenic amines may be used during cheese making to control the concentrations of biogenic amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 69 publications
1
55
1
3
Order By: Relevance
“…In a previous study, the multi-copper oxidase in lactic acid bacteria showed the potent ability to degrade BAs ( Ladero et al, 2014 ), and L. curvatus was also reported to reduce the BAs in fermented vegetable and fermented sausage ( Rabie et al, 2011 ; Mangia et al, 2013 ; Kim et al, 2017 ). Herein, all the L. curvatus strains isolated were confirmed to harbor multi-copper oxidase genes, and the sequences obtained were highly similar to that of L. paracasei CB9CT ( Guarcello et al, 2016 ). The BAs degradation test indicated that all the L. curvatus strains isolated could degrade six common BAs.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In a previous study, the multi-copper oxidase in lactic acid bacteria showed the potent ability to degrade BAs ( Ladero et al, 2014 ), and L. curvatus was also reported to reduce the BAs in fermented vegetable and fermented sausage ( Rabie et al, 2011 ; Mangia et al, 2013 ; Kim et al, 2017 ). Herein, all the L. curvatus strains isolated were confirmed to harbor multi-copper oxidase genes, and the sequences obtained were highly similar to that of L. paracasei CB9CT ( Guarcello et al, 2016 ). The BAs degradation test indicated that all the L. curvatus strains isolated could degrade six common BAs.…”
Section: Discussionmentioning
confidence: 79%
“…In lactic acid bacteria, the multi-copper oxidase showed a high ability of degrading BAs ( Guarcello et al, 2016 ). Therefore, the primers of BCf/BCr were used to detect the multi-copper oxidase gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…El hecho de que el lote 4 presente una menor concentración de aminas biógenas totales respecto al lote 3, podría estar relacionado con la capacidad de la cepa Lactobacillus plantarum TAUL 1588 para degradar las aminas biógenas producidas por las otras cepas de bacterias ácido lácticas empleadas en los cultivos. Guarcello et al (2016) han indicado que la existencia de cepas de Lactobacillus con capacidad para degradar aminas biógenas abre nuevas líneas de investigación para aumentar la disponibilidad de cultivos adjuntos para elaborar quesos. Aun así, sería necesario llevar a cabo más estudios con la cepa de…”
Section: Efecto De Cultivos Productores De Cla Y Del Tiempo De Maduraunclassified